(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study was conducted to determine the effects of Monetary Rewards on the performance of teaching staff in a higher education institution in Quezon City. Organisations are always looking at how to keep employees in the company. Also, to motivate them in their working place. Currently, most industries are adjusting to the new normal, and it is still in the recovery part. The education industry is currently adjusting to this pandemic stage. Some schools are temporarily closed and are prohibited from doing social activities. Institutions, employees, and professionals responsible for delivering knowledge to students face limitations because of health concerns during this pandemic. Most teachers conduct virtual classes to continue their duties. They are experiencing changes and creating techniques to provide the education needed in schools and students. Employees are resigning not because of losing interest in their professions but because of the new normal adjustment to the place, working environment, and routine. This includes because of the virtual practices that they are not used to. Recognising employees is very helpful in maintaining employee retention and good performance. Recognising their work and practices makes employees feel that the organisation values them. It keeps them productive. Some organisations recognise employees through certificates, publicity announcements, and money. Money is a good instrument for recognising the employee’s work because it is why employees work. They also receive additional monetary incentives for excellent performance, not part of their monthly salary. Teachers will be kept motivated, increase their performance in teaching students, and may also increase job satisfaction by seeing the achievements of their students, learning skills, and personal growth. Monetary rewards are an effective technique for the institution to keep the employees motivated and maintain the excellent performance of the teachers. These are the ways to have good motivation for the employees.